COMPARISON OF EFFECTIVENESS OF MELOXICAM 15 MG ONLY, COMBINATION OF MELOXICAM 15 MG AND TAMSULOSIN 0.4 MG, AND TAMSULOSIN 0.4 MG ONLY FOR SUCCESS OF TWOC IN BPH PATIENTS WITH FIRST EPISODE OF ACUTE URINARY RETENTION - Yasa, Muhammad Asro Abdih; Soebadi, Doddy M; Rizaldi, Fikri (Indonesian Urological Association, 2018)
Objective: To prove that Meloxicam 15 mg only, combination of Meloxicam 15 mg and Tamsulosin 0.4 mg were more effective for the success of Trial Without Catheter (TWOC) in BPH patients with first episode of urinary retention compared to Tamsulosin 0.4 mg only. Material & methods: Benign Prostatic Hyperplasia (BPH) patients with first episode of urinary retention that met the inclusion criteria and did not fulfill the exclusion criteria were randomized to form 3 treatment groups, n=11 for each group. Group I was given Meloxicam 15 mg only, group II was given a combination of Meloxicam 15 mg and Tamsulosin 0.4 mg, and group III was given Tamsulosin 0.4 mg only. For each group the drug given once orally for 7 days. The success of TWOC assessed by an ability to spontaneous micturition after that each treatment in the first 24 hours after urethral catheter removal, accompanied by Qmax in uroflowmetry ≥ 5 cc/sec and PVR ≤ 100 cc. Results: All Meloxicam 15 mg only group samples have recurred urinary retention (100%). The success rate of TWOC for combination of Meloxicam 15 mg and Tamsulosin 0.4 mg group was 72.7%; while for the Tamsulosin 0.4 mg only one was 63.6%. The success rate of TWOC for combination of Meloxicam 15 mg and Tamsulosin 0.4 mg group was higher than Tamsulosin 0.4 mg only one (p=0.003). Conclusion: The combination of Meloxicam 15 mg and Tamsulosin 0.4 mg orally once daily for 7 days was more effective in the success of TWOC in BPH patients with first episode of urinary retention compared to Tamsulosin 0.4 mg only orally once daily for 7 days.